Does Internet use connect smallholder farmers to a healthy diet? Evidence from rural China - Yang, Mingwei; Zhang, Zhiyong; Wang, Zheng (Frontiers in Nutrition, 2023)
Undernutrition and micronutrient malnutrition remain problems of significant magnitude among small-scale subsistence farmers, posing a serious threat to their health and well-being. Developing a healthy diet can effectively reduce this threat. Fortunately, the internet can speed up the process. However, it is not clear whether and by what mechanism the Internet use optimizes the dietary quality of smallholder farmers. This study uses data from 5,114 farm households in 9 provinces in China to quantitatively assess the impact of the Internet use on dietary quality. The results show that Internet use can significantly contribute to dietary diversi-ty and dietary rationality among smallholder farmers, thus optimizing their dietary structure. We also found that Internet use significantly increased the average consumption amounts of milk and its products (2.9 g), fruits (21.5 g), eggs (7.5 g), and vegeta-bles (27.1 g), while also decreasing the intake of salts (1.5 g) and oil (3.8 g). In addition, the pull of internet use to improving diet quality is more significant for smallholder households with lower levels of education, older heads of household and higher household incomes. A possible mechanism is that Internet use increases household income and information access skills of rural resident, thus improving their dietary quality. In summary, governments should further promote Internet penetration in rural areas for health purposes.